(untitled) (Al-Aasar, 2025)
The main goal of this research is to concentrate on the feminist study of Henrik Ibsen’s famous play A Doll’s House. Henrik Ibsen was a great dramatist and a well-known poet of 19th century. Social issues were the major themes of his most plays. Ibsen has raised his voice in favor of women and women’s rights in this famous play A Doll’s House. Critical Discourse Analysis is an approach that examines the connections between language and socio- political aspects in which it is used. It investigates issues like gender, politics, race, economy, religion etc. which are connected with the use of language in social setting. The present study does the critical discourse analysis of Ibsen’s well-known play A Doll’s House. The results of this study are based on CDA model of Van Dijk. According to Van Dijk’s CDA primarily studies the way social power abuse, supremacy, and discrimination are endorsed, replicated, and repelled by text and talk in socio-political contexts. The findings of this study reveal that Van Djik’s model is equally fit to comprehend the writer’s perception of feminism in written texts. The researcher will explore of how and to what degree Ibsen, one who mostly famous for his dramas and too been accredited for his feminist characters how he deals with women’s issues and how he appreciates women’s struggle. Through the Character of Nora Helmer his conception for the equality is presented subsequently in this play. The researcher will conclude with the justification how Henrik Ibsen through his female characters try to show some common problems faced by women in patriarchal society and how these women are struggling very harder to escape from this trouble.